Optimization of bread quality with quinoa flour of different particle size and degree of wheat flour replacement - KUREK,Marcin Andrzej (2020)
Abstract The study aimed to assess the influence of quinoa flour of different particle size and degree of wheat flour replacement on dough and bread characteristics. Dynamic rheology and farinographs were used to describe the dough parameters. Specific volume, texture, porosity, color, overall quality and chemical assessment were performed as well. It could be observed that the degree of wheat flour substitution by quinoa flour significantly influenced the G’ and G” values in linear and quadratic terms (p ≤ 0.01 and p ≤ 0.05). Particle size played a significant role in increasing G’ and G” only in quadratic terms. Increasing quinoa substitution of wheat flour and interaction of PS and QS significantly increased the porosity of breadcrumbs. Moisture content was mainly affected by the particle size of quinoa flour and increased the values of this parameter. The optimization revealed that the most suitable combination would be the composition of bread with 219 μm and 5.41% of substitution.